The Mawlid Tradition of Muhammad in Sudan - Mabrur, Muhamad Shofwan; Dou, Ahmad; Fadhlurrahman, M. Bintang (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Sufi in Sudan have the unique ways of preaching and spiritual practices, contributing to Sudan's reputation as the "land of a thousand Dervishes." The religious spirit in Sudan fosters a deep love for the Quran and unique traditions that reflect their faith in murshids and the Prophet's descendants. This study aims to provide an overview and mufassir interpretation of the tradition of the Prophet Muhammad's Mawlid in Sudan, which is unique compared to other countries. This research is qualitative, with the characteristics of dissecting documents and several journal articles that match. The author also took data from various articles in the mass media and journals to strengthen this research information. This type of research is library research and different kinds of unstructured interview methods by various sources. The results of this study show that the celebration of the birthday of the Prophet Muhammad in Sudan has its uniqueness, including setting up tents in the field filled with various congregations. It is filled with readings of suluk, poetry, and stories of the Prophet Muhammad's missionary struggle. Then, one of the mufassir's interpretations of this tradition, namely As-Suyuti. He believed that traditions like this are a profound gratitude to God, the creator of His creatures, Allah, for the birth and creation of humans as a mercy for the entire universe.